Characterization of the impact on the society of the local cisco networking academy of ITSA in Barranquilla - Hernandez, Leonel; Marchena, Piedad; Wibawa, Aji Prasetya (Association for Scientific Computing Electrical and Engineering, 2020)
By 1997, Cisco Systems, a company already consolidated in the technology and communications market, saw the need to train personnel who had the skills to configure, manage, install and support all its products in general at all levels, from design to the implementation of solutions. In Colombia, more precisely in the city of Barranquilla, the ITSA University Institution in the early 2000s saw an excellent opportunity to ally with the University created by Cisco, called Cisco Networking Academy, to train professionals in the Caribbean region capable of face the new challenges that technology in networks is generating day by day, becoming in the first Institution of higher education in the region to provide this type of training with international certification and endorsement. From then on, the local Cisco academy has strengthened and significantly impacted local society, generating valued and skilled labor in the labor market of the city and the region. The purpose of this work is to measure this impact, focused on the Cisco, CCNA, and CCNP flagship courses between 2015 and 2019, verifying how ITSA, through the Cisco Academy, has transformed lives. The research methodology is descriptive, exploratory, and documentary